Vitamin D enhances antiviral responses in dengue virus-infected macrophages by modulating early-response gene expression - Yordi Sebastián Tamayo-Molina; Juan Felipe Valdés-López; Geysson J. Fernandez; Silvio Urcuqui-Inchima (PLoS ONE, 2025)
Dengue virus (DENV), the etiological agent of dengue fever, remains a global health concern, leading to severe illness and death in the absence of any definitive cure. Research has shown that vitamin D may reduce DENV replication in vitro and that dengue patients with low or deficient vitamin D levels are at higher risk of severe dengue. Studies indicate that viral replication is inhibited in human monocyte-derived macrophages (MDM) differentiated in the presence of vitamin D (D3MDM), suggesting that vitamin D may prevent DENV entry into host cells. However, despite these findings, the role of vitamin D in regulating the temporal expression patterns of genes as early, mid, and late transcriptional profile of DENV-infected macrophages remains unclear. Therefore, utilizing a kinetic transcriptomic profile is crucial. This approach provides detailed insights into the dynamic changes in gene expression over time, helping to clarify how vitamin D can modulate the immune response at critical stages of DENV infection. To address the transcriptional dynamics, we conducted a comprehensive analysis of gene expression patterns in MDM and D3MDM infected with Dengue virus serotype 2 (DENV-2). Utilizing bulk RNA sequencing alongside a standard viral growth curve, we systematically analyzed transcriptional kinetics by selecting key time points: 1.5, 3, 5.5, and 10 hours post-infection (h.p.i.) to monitor early viral entry and replication events and 24 h.p.i. to assess gene expression during peak viral particle production. Our temporal analysis revealed a progressive increase in cellular transcripts within the first hour of infection, with a more pronounced gene expression pattern in DENV-2-infected MDM compared to DENV-2-infected D3MDM at this early stage. Enrichment analysis indicated a reduced inflammatory response in DENV-2-infected D3MDM. Additionally, transcription factor analysis suggested diminished NF-κB signaling, but enhanced IRF5 activity was elevated in the DENV-2-infected D3MDM. High-dimensional clustering analysis identified nine unique gene clusters across both macrophage types, with notable upregulation of genes associated with antiviral activity, including IDO1, ISG20, OASL, IFI44L, RSAD2, IFIT1, MX1, EPSTI1, CXCL10, and CXCL11 in DENV-2-infected D3MDM at 1.5 h.p.i., suggesting an enhanced early antiviral response. These findings indicate that vitamin D modulates the magnitude and diversity of the early transcriptional responses, highlighting its potential as a therapeutic option to mitigate DENV severity.